Adaptation and validation of the Berkeley Expressivity Questionnaire among Chinese international students in Malaysian higher education - Xu, Min; Yang, Xiaohan; Jaffri, Hadijah; Wong, Boon Yew (Frontiers in Psychology, 2025)
This study investigates the psychometric properties of the Berkeley Expressivity Questionnaire (BEQ) within a cross-cultural framework, specifically among Chinese international students in Malaysia. Exploratory factor analysis identified a four-dimensional structure that diverges from the original three-factor model. This new structure was subsequently validated through confirmatory factor analysis (N = 300), yielding superior model fit indices compared to alternative models, all exceeding conventional benchmarks. The findings highlight significant cross-cultural distinctions, notably in emotional concealment, reflecting the complex interplay between traditional Chinese cultural values and the demands of international educational environments. Detailed analyses indicated that specific adaptations in item wording and context were essential to achieve cross-cultural measurement validity. This research contributes to the methodological discourse on cross-cultural measurement and enriches understanding of emotional expression dynamics among international students. It underscores the importance of culturally responsive adaptations when employing Western-developed assessment tools across diverse populations. The proposed four-dimensional framework offers a refined perspective on emotional expressivity in multicultural educational contexts, providing valuable insights for enhancing the support structures aimed at improving adaptation and psychological well-being for Chinese international students.